Sphenoid Sinus Involvement in Chronic Rhinosinusitis Without Polyps. (June 2020) - Sumaily, Ibrahim; Alarifi, Ibrahim; Alahmari, Abdussalam; Aloulah, Mohammad; Alsaleh, Saad
Background: Chronic rhinosinusitis (CRS) is a common chronic disease. It has 2 main clinical subtypes: CRS with nasal polyposis (CRSwNP) and without nasal polyps (CRSsNP). The sphenoid sinus appears to be less frequently involved in CRSsNP cases. Thus, we aimed to compare the incidence of sphenoid sinus involvement between CRSsNP and CRSwNP cases. Methods: A retrospective chart review of CRS cases was performed. The clinical and imaging findings, including age, sex, adenoid, and inferior turbinate hypertrophy (ITH), deviation of the nasal septum (DNS), presence of polyps, Lund–McKay scores, and the final diagnosis, were assessed. The incidence of sphenoid sinus involvement in each CRS subtype and its correlation with the aforementioned variables were studied. Results: Of the 289 cases, 151 met the inclusion criteria including 82 CRSwNP and 69 CRSsNP cases. The mean patient age was 35.48 ± 11.88 years. The incidence of men and women were 66.9% and 33.1%, respectively. The sphenoid sinus involvement was 89% and 65.2% in the CRSwNP and CRSsNP cases ( P  = .0001), respectively. The involvement of other paranasal sinuses showed no statistically significant differences between the 2 phenotypes. No other evaluated variables, including age, gender, DNS, ITH, or adenoid hypertrophy, significantly correlated with the incidence of sphenoid sinus involvement. Conclusions: This is the first study to demonstrate that the sphenoid sinus is less frequently involved in CRSsNP cases. Further studies should investigate the underlying factors causing the lower incidence of sphenoid sinus involvement in CRSsNP.